Analysis of Digital English Dictionary Used by Students of SMP Swasta Bunga Mawar Gunungsitoli - Nopianus Gea; Yaredi Waruwu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Dictionary has an important role in the language learning process while the dictionary is used as a learning tool. As a learning tool, dictionary can be used independently because there a lot of features in it such as structure, word order, types of words, meaning and pronunciation. At present, dictionaries available in two versions, they are printed and digital versions which can be in the form of websites or applications. The aim of this research is to find out the use of English digital dictionaries by secondary students, especially students ninth grade of SMP Swasta Bunga Mawar Gunungsitoli. Based on the results of interviews with informants and a questionnaire administered to 20 students, this study used a qualitative descriptive method with data analysis. The results of the study found that digital dictionaries are used for language learning, translation and to improve English knowledge. It is strongly suggested to government to give access to the internet since those dictionaries sometimes use network. The developer of the application is also encouraged to make it accessible offline. The research also suggest for future researcher to find out about the effect of using a digital dictionary on English learning.